Recent morphological changes of the Yellow River (Huanghe) submerged delta: Causes and environmental implications - Jiang, Chao; Pan, Shunqi; Chen, Shenliang (Geomorphology (Amsterdam, Netherlands), 2017)
The Yellow River (Huanghe) submerged delta (YRSD) has been under the threat of erosion and retreat during the Anthropocene due to dramatic climatic and anthropogenic changes in the Yellow River basin. The analysis of field data shows that over the period of 1977–2005, the changes in climate (decrease in precipitation and increase in air temperature) and human interventions (increase in water diversion projects) throughout the watershed have resulted in the sharp reductions of river flow and sediment discharges into the Bohai Sea. Consequently, over the decadal timescale, morphological evolution of the YRSD has gone through three stages: i.e. rapid accumulation (5.77×108m3/year) in 1977–1985, moderate accumulation (3.80×108m3/year) in 1986–1995 and slow accumulation (0.91×108m3/year) in 1996–2005. Climatic change within the catchment characterized by the rapid increase of air temperature contributed significantly to the transitions from the rapid accumulation to the moderate accumulation, and to the subsequent slow accumulation. The decadal morphological changes of the YRSD also show peculiar deposition/erosion characteristics over the medium timescale under river input reduction. Within the three decades, the patterns of the main sedimentary body exhibit irregular ellipses with the long axis parallel to the −5 or −10m isobaths and short axis perpendicular to the isobaths. The depocentres of the YRSD are located between the −10 and −15m isobaths close to the respective river mouths, with a high vertical accretion rate of ~1.20m/year. The time series data of annual volumetric change of the YRSD and river sediment load from 1977 to 2005 further demonstrate significant linear positive relationships between deltaic geomorphic change and fluvial input over shorter timescales (annual and 3-year). The critical sediment discharges for maintaining the deposition/erosion equilibrium state of the YRSD over the annual and 3-year timescales are found to be 1.79×108t/year and 1.29×108t/year, respectively. The analysis from the latest hydrological data (2006–2015) suggests that over the decadal timescale, the evolution state of the YRSD currently has transitioned from constructive to destructive due to the weakened fluvial input. Moreover, there exists a close quantitative link between the progradation of the Yellow River subaerial delta (YRAD) and the YRSD over the five-year timescale, indicating that every 1×108m3/year increase of the YRSD's yearly volumetric change will result in a 3.28km2/year increase of the YRAD's yearly land-accretion area, and the YRAD will reach the extension/retreat balance state when yearly morphological change of the YRSD is at 0.73×108m3/year. •The Yellow River Submerged Delta (YRSD) has successively went through rapid, moderate and slow accumulation stages during 1976-2005.•Stage transition is strongly associated with climate-induced fluvial supply decrease.•The YRSD’s depocenter maintains a high-rate of deposition under river input reduction.•Evolution state of the YRSD currently has transitioned from constructive to destructive.•A clear link exists between the progradation of the subaerial and submerged deltas.